Pengaruh Disiplin Kerja Terhadap Kinerja Aparatur Sipil Negara (ASN) Dinas Pendidikan Dan Kebudayaan Kabupaten Kampar - Radiyah; Sri Indrastuti; Lilis Suryani (Jurnal Ekonomi KIAT, 2016)
Apparatus State Civil Servants as a key element of human resources of the state apparatus have a role in determining the success of govermance and development. The figure employee Apparatus State Civil.which is able to play that role in this research is a Civil Servant who has competence indicated from the discipline that high, good performance and the attitudes and behavior that are full of loyalty and obedience to the state, morals and mentality good, professional, aware of its responsibilities as a public servant as well as capable of being the glue of national unity. This study aims to identify and analyze the discipline of work and performance of Civil Servants in the Education and Culture Kampar District and determine the effect of labor discipline on the performance of the Civil Service in the Department of Education and Culture of Kampar District. This type of research is descriptive research with quantitative methods. Respondents in was a Civil Servant in the Department of Education and Culture of Kampar District and key informants in this study consists of the Head of Department, Head of Public and Civil, Head of Basic Education and the Head of the Basic Education Curriculum. Data collected by observation, questionnaires and interviews with key informants. To see the effect of labor discipline on the performance of the Civil Service at the Department of Education and Culture of Kampar District used statistical analysis. Based on the survey results revealed that the discipline of work and performance of Civil Servants in the Education and Culture Kampar District is considered to be good. Analysis with SPSS showed that the Disciplinary Work has a strong connection to the Civil Service Performance. Labor discipline positive effect on performance Civil Servants, so any improvement to the discipline of work, it will be able to improve the performance of Civil Servants in the Education and Culture Kampar District.